Staff Profile: Dr. Lynette Mukami Nthiga - Lynette, Mukami Nthiga (UoEm, 2024)
I am a graduate of Law with knowledge in International Law, strategic advocacy and policy analysis. I am a consultant, a researcher, and an academic in: Policy & Law. I am also experienced in working in diverse and dynamic environments. I am keen and passionate on interdisciplinary interactions of law and policy development.